Surface dissolved nitrous oxide concentrations during SONNE cruise SO303 - Arévalo-Martínez, Damian L; Sommer, Marcel; Bange, Hermann W; Eisnecker, Paula; Schulz, Gesa; Stoltenberg, Ina (PANGAEA, 2025)
The dataset comprises high-resolution (1-min) measurements of dissolved nitrous oxide in surface waters of the Eastern Tropical Indian Ocean. The observations were conducted during the expedition SO-303 on board R/V SONNE (January-February 2024). Seawater was drawn on board by means of a submersible pump installed at 6 m depth, and measurements of equilibrated headspace were carried out as described in Arévalo-Martínez et al. (2013): https://doi.org/10.5194/os-9-1071-2013.
Keywords: N2O; N2O emissions; Tropical Indian Ocean